2013
DOI: 10.1097/ncc.0b013e3182642d7c
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Dyadic Peer Support Intervention for Newly Diagnosed Breast Cancer Patients in Korea

Abstract: Oncology nurses are optimally positioned to promote adjustment in patients with cancer. Trained peer support partners, supervised by skilled nurses, may be useful in improving self-efficacy of patients newly diagnosed with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 34 publications
1
62
0
Order By: Relevance
“…Lee et al . () examined a dyadic peer support intervention for newly diagnosed breast cancer patients in South Korea and Schover et al . () assessed Sisters Peer Counseling in Reproductive Issues After Treatment, a sisters peer counselling programme for African‐American breast cancer patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al . () examined a dyadic peer support intervention for newly diagnosed breast cancer patients in South Korea and Schover et al . () assessed Sisters Peer Counseling in Reproductive Issues After Treatment, a sisters peer counselling programme for African‐American breast cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al . () also found a significant difference in changes in self‐efficacy for self‐management of breast cancer between an experimental group (dyadic peer intervention) and a control group (CG; treatment as usual); however, no significant changes were observed regarding psychological distress (anxiety and depression) and adjustment between the two groups.…”
Section: What Are the Objectives And Outcomes Of Studies Assessing Onmentioning
confidence: 90%
“…RCTs have shown improvements in self-efficacy for patients with breast cancer and prostate cancer, respectively [15,16]. In a review of 44 studies on peer-support programs in cancer care, Hoey et al concluded that one-on-one face-to-face, and group internet, peer-support programs were the most effective [9].…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…There is evidence of improved psychological wellbeing for the recipients of such support [2][3][4], however, findings are inconsistent. It may be that individual characteristics determine who benefits from peer support, and these individual variations may be lost in aggregated data.…”
mentioning
confidence: 85%